Supercritical Solvent Impregnation of Different Drugs in Mesoporous Nanostructured ZnO - Mauro Banchero; Sara S. Y. Mohamed; Federica Leone; Francesca Lopez; Silvia Ronchetti; Luigi Manna; Barbara Onida (MDPI AG, 2019)
Supercritical solvent impregnation (SSI) is a green unconventional technique for preparing amorphous drug formulations. A mesoporous nanostructured ZnO (mesoNsZnO) carrier with 8-nm pores, spherical-nanoparticle morphology, and an SSA of 75 m2/g has been synthesized and, for the first time, subjected to SSI with poorly water-soluble drugs. Ibuprofen (IBU), clotrimazole (CTZ), and hydrocortisone (HC) were selected as highly, moderately, and poorly CO2-soluble drugs. Powder X-ray diffraction, Fourier transform infrared spectroscopy, field emission scanning electron microscopy, nitrogen adsorption analysis, and ethanol extraction coupled with ultraviolet spectroscopy were employed to characterize the samples and quantify drug loading. Successful results were obtained with IBU and CTZ while HC loading was negligible, which could be related to different solubilities in CO2, drug size, and polarity. Successful SSI resulted in amorphous multilayer confinement of the drug. The mesoNsZnO-IBU system showed double drug loading than the mesoNsZnO-CTZ one, with a maximum uptake of 0.24 g/g. Variation of contact time during SSI of the mesoNsZnO-IBU system showed that drug loading triplicated between 3 and 8 h with an additional 30% increment between 8 h and 24 h. SSI did not affect the mesoNsZnO structure, and the presence of the adsorbed drug reduced the chemisorption of CO2 on the carrier surface.